Monetary Transmission in Low Income Countries - Montiel, Peter (IMF Working Papers; Working Paper ;, 2010)
This paper reviews monetary transmission mechanisms in low-income countries (LICs) to identify aspects of the channels that may operate differently in LICs relative to advanced and emerging economies. Given the weak institutional frameworks, reduced role of securities markets, imperfect competition in the banking sector and the resulting high cost of bank lending to private firms, the traditional channels (interest rate, bank lending, and asset price) are impaired in LICs. The exchange rate channel is also undermined by central bank intervention in the foreign exchange market. These conclusions are supported by review of the institutional frameworks, statistical analysis, and previous literature.